The Development of the Brief Sexual Performance Anxiety Scale - Kochenour, Allysha; Griffith, James D. (Advances in Social Sciences Research Journal, 2020)
Performance anxiety impairs attention, increases avoidant behaviors, and is associated with negative evaluations of the self. Relating to sexual experiences, performance is adversely affected by anxiety. Scales measuring the construct of anxiety specifically related to sexual performance are lacking. A series of three studies were conducted in an effort to develop a brief measure of sexual performance anxiety. The current study (N = 530 across three samples) developed and evaluated the psychometric properties of the Brief Sexual Performance Anxiety Scale (BSPAS). An exploratory factor analysis yielded an 8-item instrument that was shown to be a single-factor construct which accounted for 52% of the variance. Cronbach’s alpha was assessed during each study and ranged from .87 - .90. Acceptable test-retest reliability over a 4-week interval was also obtained. A confirmatory factor analysis provided evidence that the unidimensional model of the scale fit the data well. The instrument also showed reasonable convergent, discriminant, concurrent, and predictive validities. The BSPAS was created to be an inclusive instrument that can be used to assess sexual performance anxiety in adults across gender, age, sexual orientation, and culture which may be useful to researchers, clinicians, and sex educators.